2009
DOI: 10.1007/978-1-4419-1440-8_1
|View full text |Cite
|
Sign up to set email alerts
|

Bioconcentration, Bioaccumulation, and Metabolism of Pesticides in Aquatic Organisms

Abstract: The ecotoxicological assessment of pesticide effects in the aquatic environment should normally be based on a deep knowledge of not only the concentration of pesticides and metabolites found but also on the influence of key abiotic and biotic processes that effect rates of dissipation. Although the bioconcentration and bioaccumulation potentials of pesticides in aquatic organisms are conveniently estimated from their hydrophobicity (represented by log K(ow), it is still indispensable to factor in the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
111
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(118 citation statements)
references
References 594 publications
(639 reference statements)
4
111
0
3
Order By: Relevance
“…For example, (Smith et al (2010) demonstrated that hepatic metabolism of fluoxetine in trout was limited unless induced by pre-exposure to carbamazepine. In fact, limited information exists on invertebrate metabolism of organic chemicals (Katagi, 2010); however, biotransformation by the invertebrate G. pulex has been to shown to alter internal concentrations of xenobiotics . Clearly, an advanced understanding of biotransformation of pharmaceuticals in fish, invertebrate, plant and periphytic communities is needed to improve bioaccumulation assessments .…”
Section: Pharmaceutical Bioaccumulation By Periphyton and Invertebratmentioning
confidence: 99%
“…For example, (Smith et al (2010) demonstrated that hepatic metabolism of fluoxetine in trout was limited unless induced by pre-exposure to carbamazepine. In fact, limited information exists on invertebrate metabolism of organic chemicals (Katagi, 2010); however, biotransformation by the invertebrate G. pulex has been to shown to alter internal concentrations of xenobiotics . Clearly, an advanced understanding of biotransformation of pharmaceuticals in fish, invertebrate, plant and periphytic communities is needed to improve bioaccumulation assessments .…”
Section: Pharmaceutical Bioaccumulation By Periphyton and Invertebratmentioning
confidence: 99%
“…Among the most toxic pesticides are the organochlorine pesticides, recognized to have potential to induce hormonal disruption and cancer (Ehrlich et al 2011;Mearns et al 2012;Vallack et al 1998), mainly due to their extreme persistency, bioaccumulating and/or rippling through the food chain (Chopra et al 2011;Katagi 2010). So, the abusive use of pesticides and inefficient treatment of residues increase their probability of reaching estuarine and marine environments affecting fish nurseries as well as the benthic and pelagic communities (Liu et al 2008;McMillin and Means 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The gap in knowledge related to mechanisms required to process nutrients in marine herbivorous fishes, for example, has only recently begun to close (Choat and Clements, 1998;Clements et al, 2009). Moreover, despite a long history of investigating how aquatic animals process chemical contaminants (Chambers and Yarbrough, 1976;Katagi, 2010;Rewitz et al, 2006;Smital et al, 2004), studies investigating how they process dietary secondary metabolites have only recently been initiated (Gross and Bakker, 2012;Liang et al, 2007;Richardson et al, 2009). An understanding of pharmacology can fill these gaps in both terrestrial and aquatic systems.…”
Section: Pharmacological Mechanismsmentioning
confidence: 99%